Peningkatan Daya Saing UMKM Waroeng Garazie melalui Pendampingan Promosi Visual dan Analisis Studi Kelayakan Usaha - Tri Difastio Ramadhan; Faqih Aji Prabowo; Feby Lasmaria Butar Butar; Naura Fahira Kesuma Putri; Resha Moniyana; Joni Putra; Yohanes Novi Armunanto (Jurnal Ekonomi dan Bisnis Digital, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in supporting local economies, yet many still face challenges in management, promotion, and legal compliance. This community service project was conducted at Waroeng Garazie, a culinary MSME based in Kalianda, South Lampung, aiming to enhance its business capacity and competitiveness. The approach involved direct observation, needs assessment discussions, the creation of promotional media, and the introduction of basic business feasibility concepts. The results showed improved understanding among business owners regarding the importance of financial recording, strengthening brand identity, and applying more effective marketing strategies. Future development is recommended to focus on digital marketing, simple application-based financial recording, and stronger branding to ensure sustainable business growth for Waroeng Garazie.